Educação científica e cidadania: as diferentes concepções e funções do conceito de cidadania nas pesquisas em Educação em Ciências - Toti, Frederico Augusto (Universidade Federal de São Carlos, 2011)
The participating citizenship so central to the goals proclaimed Science Education in the 21 th century. However, there are different conceptions of its meaning and different relations between Science Education and citizenship, not always reconcilable. Despite this, little is clear about the ideas related to citizenship in the research papers in Science Education. Through a survey of theoretical and literature based on elements of Sociology, are characterized these different conceptions of citizenship and functions of the relations between Science Education and citizenship, from articles published in periodicals of international circulation, the area of Science Education. The results lead to significant debates about the relationship between Science Education and citizenship. The functions of these relationships, we analyzed papers seized, have common elements despite presenting itself in different conceptions of citizenship. The analysis suggests that the papers are reflected in four core ideas that currently influence the Science Education in the context of citizenship. These core ideas have been characterized and named: the emergence of a citizenship impulse; emergence of a cognitive impulse; emergence of environmental issues, the emergence of multicultural issues.
Keywords: Educação; Educação em Ciências; Cidadania; Pesquisas em Educação em Ciências; Science education; Citizenship; Research in science education; CIENCIAS HUMANAS::EDUCACAO